Comparative investigation on the value-added products obtained from continuous and batch hydrothermal liquefaction of sewage sludge - Fan, Yujie; Prestigiacomo, Claudia; Gong, Miao; Tietz, Thomas; Hornung, Ursel; Dahmen, Nicolaus (Frontiers in Environmental Science, 2022)
Hydrothermal liquefaction (HTL) can be considered a promising route for the energy valorisation of waste sewage sludge (SS). However, not much information is available on continuous flow processing. In this study, the mixed SS was subjected to HTL at 350 °C for 8 min in a continuous reactor with loadings of 10 wt.% in the feed flow. The results show that the mass recovery reached 88 %, with a biocrude yield of 30.8 wt.% (3.9 wt.% N content). The recovered biocrude yields are highly dependent on the selection of the recovery solvent for extraction, and dichloromethane can contribute an additional 3.1 wt.% biocrude from aqueous phase, acetone can extract some pyrrole derivatives into the trapped phases. Comparable results were also achieved by performing batch reactions under the same conditions: a slightly higher biocrude yield (33.1 wt.%) with an N content of 4.3 wt.%. The higher N content observed in the biocrude from the batch process indicates that interactions and chelation between intermediates are enhanced during heating up and cooling period, which lead to more N-containing compounds.